Professional troublemaker the fear fighter manual - Luvvie Ajayi Jones (New York Viking, 2021)
"With humor and honesty, and guided by the influence of her inspiring and professional troublemaking grandmother, Funmilayo Faloyin, Luvvie walks us through what we must get right within ourselves before we can do the things that scare us; how to use our voice for a greater good; and how to put movement to the voice we've been silencing--because truth-telling is a muscle. The point is not to be fearless. It is to know we are afraid and to charge forward regardless, to recognize the things we must do are more significant than the things we are afraid to do. This book shows you how she's done it, and how you can, too"-- Provided by publisher.
Keywords: Self-confidence.